Europeanization and the extreme right in Bulgaria and Turkey: Unveiling similarities between Ataka party and red apple coalition - (:unkn) unknown (My University, 2011)
This article aims at comparing the main characteristics of the extreme right groups in Turkey and Bulgaria. The ATAKA party in Bulgaria and the Red Apple Coalition in Turkey are chosen for comparison. There has been an increasing convergence of the discourse and strategy of these groups in reaction to globalization in general, and the Europeanization process in particular. This article will test the validity of this hypothesis, without neglecting the differences caused by the individual histories of the two countries. The chosen groups' attitudes towards significant political issues, as well as their discourse and strategy, will be analyzed with comparative insight. © 2011 Brill.
Keywords: ATAKA; EUROPEANIZATION; EXTREME RIGHT; POPULISM; RED APPLE COALITION